AB0144 Pregnancy outcomes in immune-mediated rheumatic diseases: a retrospective longitudinal study in a tertiary hospital. (15th June 2017) - Bernardo, J; Brito, I; Guimarães, H; Guimarães, M; Fonseca, R
Abstract : Background: Autoimmune rheumatic diseases such as systemic lupus erythematosus (SLE), antiphospholipid antibody syndrome (APS) and Sjögren's syndrome (SS) are part of a clinical spectrum eligible to affect women in child-bearing ages, increasing pregnancy morbidity and affecting neonatal outcomes. Pregnancy complications include the teratogenic risk from immunosuppressive drugs, pregnancy-related disease flares, recurrent pregnancy loss, premature delivery, intrauterine growth restriction (IUGR) and preeclampsia. Conceiving in periods of low disease activity helps to reduce these complications. Objectives: This project aims to describe the occurrence of pregnancy complications among women with immune-mediated rheumatic diseases and to study the associated clinical factors. Methods: A retrospective longitudinal study was performed including consecutive pregnant women with immune-mediated rheumatic diseases seen in a multidisciplinary group for autoimmune diseases during pregnancy, in a tertiary hospital, between January 2010 and December 2015. Clinical and demographic data, as well as and pregnancy outcomes, were collected through consultation of clinical files. The factors associated with pregnancy manifestations (premature delivery, flares during pregnancy, recurrent pregnancy loss and foetal growth restriction) were studied using Mann-Whitney, qui-square and fisher tests (SPSS 24.0). Significance level was set as <0.05. Results: We included 151 gestations from a total of 140 women with a mean age of 32, 5±4, 4 years; 4 gestations were twin pregnancies. Within these 151 gestations, 54 (35, 8%) women had SLE, 17 (11, 3%) had Sjögren's syndrome, 17 (11, 3%) had rheumatoid arthritis, 41 had APS (27, 2%), 11 (7, 3%) had Behçet's disease, 4 (2, 6%) had systemic sclerosis, 8 (5, 3%) had mixed connective tissue disease and 16 (10, 6%) had other immune-mediated diseases. 35 (23, 2%) had anti-SSA/La antibodies, 18 (11, 9%) had anti-SSB antibodies, 6 (4, 0%) had anti-URNP antibodies and 43 (28, 5%) had anti-nuclear antibodies. Seven (4, 6%) of the women developed gestational diabetes and 4 (2, 6%) developed gestational hypertension. Furthermore, 54 (35, 8%) women had had previous miscarriages. Prematurity occurred more frequently among neonates with IUGR (53.8% vs 46.1%; p=0.04), and was associated with gestational diabetes (21.4% vs 2.9%; p=0.018). It also occurred more frequently in multiple pregnancies (75% vs 16.4%; p=0.001), mothers taking glucocorticoids (28.6% vs 9.2%; p=0.003) and active rheumatic disease at conception (23% vs 6.8% p=0.03). No statistically significant differences were observed in the occurrence of different pregnancy complications among different diseases or in presence of different antibodies. Conclusions: Our study proved a link between immune-mediated rheumatic diseases and specific pregnancy outcomes such as prematurity and IUGR. Outcomes were worse when taking glucocorticoids, when gestational diabetes were developed and when conception occurred in a period of active disease. Disclosure of Interest: None declared